Alleviation of Salinity Hazards in Different Maize Genotypes Using Inorganic Ions (Ca++ and K+): Salinity Hazards in Different Maize Genotypes - Suhaib, Muhammad; Mujtaba, Asma; Munir, Masooma; Saqib, Zulfiqar Ahmad (Biological Sciences - PJSIR, 2020)
A hydroponic experiment was conducted to evaluate and compare the efficiency of Ca and K ions and different maize genotypes with imposed salinity. Two levels of K+ and Ca++ (5 and 10 mM) each were tested on two maize genotypes (Pioneer-3335 and Syngenta-8441) under 100 mM NaCl stress. Saline treatment adversely affected the plant physiological parameters and disturbed the ionic balance and resulted in poor plant growth. However, Syngenta-8441 was more prone to salt stress as compared to Pioneer-3335. Both of the inorganic ions showed significant effects on physiological and ionic components of both genotypes. Among the inorganic ions K was found to be more efficient than Ca in improving the plant growth. Improved physiological and ionic traits were observed more significant with 10 mM K ion treatment followed by 5 mM K. Among Ca treatments higher level of Ca (10 mM) showed more significant results as compared to 5mM Ca++. This study revealed that Ca++ and K+ both are compulsory for maintaining the crop growth because of their mutual effects under salt stress. However, the alleviative efficiency of K is far better than Calcium but its (Ca++) role could not be neglected, while regarding genotypic differential response imposes the fact that Pioneer-3335 is more tolerant to salinity menace as compared to Syngenta- 8441 but both of the genotypes were significant in their recovery from stress to applied Ca++ and K+.